Bank liquidity risk: analysis and estimates - Jasienė, Meilė; Martinavičius, Jonas; Jasevičienė, Filomena; Krivkienė, Gražina (Business, Management and Economics Engineering, 2012)
In today’s banking business, liquidity risk and its management are some of the most critical elements that underlie the stability and security of the bank’s operations, profit-making and clients confidence as well as many of the decisions that the bank makes. Managing liquidity risk in a commercial bank is not something new, yet scientific literature has not focused enough on different approaches to liquidity risk management and assessment. Furthermore, models, methodologies or policies of managing liquidity risk in a commercial bank have never been examined in detail either. The goal of this article is to analyse the liquidity risk of commercial banks as well as the possibilities of managing it and to build a liquidity risk management model for a commercial bank. The development, assessment and application of the commercial bank liquidity risk management was based on an analysis of scientific resources, a comparative analysis and mathematical calculations.